1994
DOI: 10.1111/j.1365-2044.1994.tb03576.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative nausea and vomiting

G. N. C. KENNY

Abstract: Although the aetiology of postoperative nausea and vomiting is not completely clear, a number of key contributing factors increase the risk for an individual patient. The inhalational agents are variably associated with postoperative nausea and vomiting, and nitrous oxide is particularly emetogenic. Older inhalational anaesthetics, such as cyclopropane, are associated with a high incidence, while the currently used agents, isoflurane, enflurane and halothane, cause less, but still significant postoperative nau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
142
2
13

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(161 citation statements)
references
References 52 publications
4
142
2
13
Order By: Relevance
“…Because these effects are partly prevented by anticholinergic drugs, such as atropine, it was suggested that omitting antagonism of neuromuscular block decreases the risk of PONV because anticholinergic drugs are given concomitantly with antagonism. 21 Finally, in healthy volunteers, intrathecal neostigmine caused severe nausea and vomiting in a dose-dependent manner. 22 These authors suggested that the most likely site of this adverse effect was in the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…Because these effects are partly prevented by anticholinergic drugs, such as atropine, it was suggested that omitting antagonism of neuromuscular block decreases the risk of PONV because anticholinergic drugs are given concomitantly with antagonism. 21 Finally, in healthy volunteers, intrathecal neostigmine caused severe nausea and vomiting in a dose-dependent manner. 22 These authors suggested that the most likely site of this adverse effect was in the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…The use of opioid analgesics (e.g. morphine and codeine in this study) is needed to control postoperative pain but they also increase the incidence of PONV 1,34,35 especially in outpatients who become mobile more quickly. 3 6 The use of opioid analgesics did not vary among the study groups (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The Consensus Guideline for Managing PONV classified large amount of information into five levels of evidence based on study design (I-V) and three strengths of recommendation based on expert opinion (A-C). 8 In the guideline, patient-specific risk factors include female sex (IA), nonsmoking status (IV A) and a history of PONV or motion sickness (IV A).…”
Section: Discussionmentioning
confidence: 99%
“…Some anesthetics such as nitrous oxide and volatile anesthetics including sevoflurane, supplemental agents such as opioids, neostigmine, female patient, nonsmoking status and a history of postoperative nausea and vomiting (PONV) are risk factors for PONV. 7,8 In contrast, since propofol has a strong antiemetic effect after general anesthesia, 7,8 propofol anesthesia may be a good choice for orthognathic surgery.…”
mentioning
confidence: 99%